Combustion and emission characteristics of n-butanol-gasoline blends in SI direct injection gasoline engine. (February 2020) - Tian, Zhi; Zhen, Xudong; Wang, Yang; Liu, Daming; Li, Xiaoyan
Abstract: N-butanol is a valuable renewable fuel that has been extensively studied. In this paper, the effect of n-butanol-gasoline blends on combustion and emissions performance of direct injection gasoline engine under urban conditions (throttle opening is 10% and 35%) is studied by using GT-Power simulation software. By comparing the several fuels, we find a fuel that is more suitable for the engine to operate in urban conditions. This is of great significance for reducing China's dependence on oil. The simulation results show that adding n-butanol into gasoline can significantly reduce the peak in-cylinder temperature (Tmax ), improve the brake thermal efficiency (BTE) of the engine. It is advantageous for the engine to operate under urban conditions. By comparison, it is found that Bu40 is the most suitable fuel. When the throttle opening is 10%, high engine speed operation will reduce brake power (BP), brake torque (BT) and BTE, and increase CO emissions. In terms of emissions, n-butanol gasoline blends can reduce CO and NOx emissions, but HC emissions increase. Finally, the results show that n-butanol-gasoline blends can be used in SI direct injection gasoline engine instead of pure gasoline. Highlights: The Bu40 can improve the performance of the engine and has the potential to be a fuel alternative to gasoline. The n-butanol gasoline blends can increase engine power and torque at low speeds. The result is the opposite at high speeds. N-butanol gasoline blends can improve engine thermal efficiency. N-butanol gasoline blends can reduce CO and NOx emissions, but increase HC emissions.